P0389THE PREVALENCE, CLINICAL AND PATHOLOGICAL CHARACTERISTICS OF PRIMARY FOCAL SEGMENTAL GLOMERULOSCLEROSIS IN TURKISH ADULTS: THE DATA FROM TSN-GOLD ( TURKISH SOCIETY OF NEPHROLOGY GLOMERULAR DISEASES) WORKING GROUP. (6th June 2020) - Kurultak, Ilhan; Gungor, Ozkan; Ozturk, Savas; Dirim, Ahmet Burak; Eren, Necmi; Yenigun, Ezgi; Ahbap Dal, Elbis; Dincer, Mevlut Tamer; Bora, Feyza; Akgur, Suat; Sumnu, Abdullah; Dursun, Belda; et al.
Abstract: Background and Aims: Focal segmental glomerulosclerosis (FSGS) is one of the primary glomerulopathies which is the most common cause of end-stage renal disease among all primary glomerular diseases. In adults, nephrotic syndrome develops 10-35% due to FSGS. However, its frequency has been increasing in recent years. This study was aimed to present the data and the prevalence of primary FSGS patients in Turkey. Method: These data were obtained from the National Multicenter (47 centers) Primary Glomerular Diseases registry system, which was entered into the T urkish S ociety of N ephrology G lo merul ar D iseases (TSN-GOLD) database between May 2009 and June 2019. The presented data in this study is cross-sectional and includes the recorded data of the patients in the hospitalization period for the kidney biopsy. These demographic, clinic and pathological data of patients were evaluated with using statistically. Results: Of the 3875 patients enrolled in the Primary Glomerular Diseases database, 850 (21.9%) had FSGS. The mean age of the patients was 47.1 ± 13.7 and 435 (52%) of patients were male. Two hundred and eighty one (33.1%) had hypertension and 93 (11%) had diabetes. Five hundred and four patients (59.3%) were diagnosed as nephrotic syndrome. At the time of diagnosis, the mean systolic blood pressure was 13.8 ± 18.6 mm Hg and the mean diastolic blood pressure was 81.4± 11.4 mm Hg. The laboratory findings at the time of diagnosis on following; serum creatinine 1.2 ± 0.04 mg / dl, albumin 3.3 ± 0.03 g / dl, and 24 hours urinary proteinuria amounts to 4743 ± 181 mg / day. Demographical and clinical data of the patients at the time of diagnosis were presented on Table 1. In pathological examination; the mean number of glomeruli was 16.8 ± 0.3, global sclerotic glomeruli were 3.1 ± 0.1, and segmental sclerotic glomeruli were 2.4 ± 0.1. Summary of Pathological Findings were presented on Table 2 Conclusion: It is very difficult to determine the absolute incidence and prevalence of primary FSGS. Incidence rates have been reported to range from 0.2 to 1.8 / 100, 000 per year in the literature. In a United States study, the most common diagnosis in 2501 kidney biopsies was FSGS (35.9%). According to this database, the prevalence of FSGS in primary glomerular diseases in our country is 21.9%.